Will co-trimoxazole resistance rates ever go down? Resistance rates remain high despite decades of reduced co-trimoxazole consumption. (December 2017) - Pouwels, Koen B.; Batra, Rahul; Patel, Amita; Edgeworth, Jonathan D.; Robotham, Julie V.; Smieszek, Timo
Highlights: Co-trimoxazole use in UK is dramatically lower than in the late 1980s. In older studies, decline in use did not result in decline in resistance. Mathematical models showed that it may take decades before resistance declines. Analysed more recently collected Escherichia coli blood isolates. Co-trimoxazole resistance did not decline over time between 2002 and 2014 Abstract: Objective: Several studies showed that a substantial decline in the use of co-trimoxazole did not result in a decline in resistance rates among Escherichia coli isolates. Since mathematical models have shown that it may take decades before resistance rates start to decline to relevant levels, we performed a new analysis using more recently collected data. Methods: Data were extracted from Guy's and St Thomas' Hospitals Transmission and Antimicrobial Record database which contains microbiological test results from all specimens tested between 2002 and 2014. We selected all blood samples positive for E. coli which were tested for resistance against co-trimoxazole. Prevalence of co-trimoxazole resistance among the tested samples by year was modelled by a Poisson model. Results: Almost all (96%) of E. coli blood isolates were tested for co-trimoxazole resistance. In total, 2070 E. coli isolates were available for analyses. Resistance to co-trimoxazole fluctuated over the years, but there was no clear increasing or decreasing trend; the annual percentage change in the prevalence of co-trimoxazole resistance was 0.52 (95% confidence interval −0.75% to 1.81%). Including co-trimoxazole or trimethoprim use in the year before the sample was taken did not improve the model. Conclusion: The prevalence of co-trimoxazole resistance among E. coli blood isolates remained high, almost three decades after a substantial decline in co-trimoxazole use. Our results further emphasize the importance of prudent antibiotics use, as antibiotic resistance may not always be easily reversible.